MicroRNA-145 attenuates IL-6-induced enhancements of sensitivity to UVB irradiation by suppressing MyD88 in HaCaT cells. (August 2018) - Dong, Hui; Jiang, Wei; Chen, Hongquan; Jiang, Shui; Zang, Yunshu; Yu, Bo
MicroRNAs (miRNAs/miRs) play vital roles in various immune diseases including systemic lupus erythematosus (SLE). The current study aimed to assess the role of miR-145 in interleukin-6 (IL-6)-treated HaCaT cells under ultraviolet B (UVB) irradiation and further explore the potential regulatory mechanism. HaCaT cells were pretreated with IL-6 and then exposed to UVB to assess the effect of IL-6 on sensitivity of HaCaT cells to UVB irradiation. The levels of miR-145 and MyD88 were altered by transfection and the transfected efficiency was verified by quantitative reverse transcription polymerase chain reaction (qRT-PCR)/western blot analysis. Cell viability, percentage of apoptotic cells and expression levels of apoptosis-related factors were measured by trypan blue assay, flow cytometry assay, and western blot analysis, respectively. In addition, the levels of c-Jun N-terminal kinases (JNK) and nuclear factor-κB (NF-κB) signaling pathway-related factors were assessed by western blot analysis. IL-6 treatments significantly aggravated the reduction of cell viability and promotion of cell apoptosis caused by UVB irradiation in HaCaT cells. Interestingly, miR-145 level was augmented by UVB exposure and miR-145 mimic alleviated IL-6-induced increase of sensitivity to UVB irradiation in HaCaT cells, as dramatically increased cell viability and reduced cell apoptosis. Opposite effects were observed in miR-145 inhibitor-transfected cells. Meanwhile, MyD88 was negatively regulated by miR-145 and MyD88 mediated the regulatory effect of miR-145 on IL-6- and UVB-treated cells. In addition, miR-145 mimic inhibited the JNK and NF-κB pathways by down-regulating MyD88. In conclusion, the present study demonstrated that miR-145 alleviated IL-6-induced increase of sensitivity to UVB irradiation by down-regulating MyD88 in HaCaT cells.